On the Energetically Most Efficient Trajectories for the Heavy Machine Shoving Process - Jarzębowski, A.; Maciejewski, J.; Szyba, D.; Trąmpczyński, W. (Engineering Transactions, 1995)
Taking into account theoretical predictions and preliminary test results, the experiments concerning the influence of tool trajectory on the specific energy of heavy machinery tool filling processes were performed. All experiments were carried out on a semi-laboratory scale using the special, fully automatic stand and the cohesive model soil. Tests were executed for both the laboratory-prepared horizontal and inclined slopes, using the model of the tool, which was first pushed into the slope and then "withdrawn" in various directions. Two different methods of driving out the tool were used: tool motion without rotation and with rotation, to simulate the filling process. It was found that the tool trajectories planned by means of the kinematically admissible solutions are energetically most effective.